Genetic structure of traditional cacao reveals four new genetic lineages in indigenous Amazonian sites in Peru - Lambert A. Motilal; Martha S. Calderon; Danilo E. Bustamante; David Gopaulchan; Daniel Tineo; Fanny R. Márquez-Romero; Sphyros Lastra; Jorge R. Diaz-Valderrama; Juan Carlos Guerrero-Abad; Manuel Oliva; Pathmanathan Umaharan (PLoS ONE, 2026)
Cacao genetic resources in Peru are largely uncharacterized. Knowledge of their genetic structure is needed for their conservation and use. Indigenous on-farm cacao trees (n = 390) from the Departments of Amazonas (n = 130), Ayacucho (n = 76), Cajamarca (n = 1), Cusco (n = 110), Madre de Dios (n = 10), Piura (n = 59), San Martín (n = 3) and Ucayali (n = 1) in Peru were fingerprinted with 192 single nucleotide polymorphic markers. Identity, group differentiation, phylogenetic, multivariate and ancestry analyses were conducted. Four new populations were identified guided by phylogenetic, accepted ancestral backgrounds of reference samples and least admixture among samples. The cacao from these eight Departments were variably mixed containing both pure members of new populations and admixed samples with these new populations and Amelonado, Contamana, Criollo, Curaray, Guiana, Iquitos, Marañon, Nacional, Nanay and Púrus. The findings of this study suggest that while the cacao germplasm is genetically related across different departments, each region harbors its own distinct genetic composition. The Clade IV (Chuncho 2) population was associated with the Contamana cluster and Clade I (Chuncho 1) was associated with Purus cluster. Clades II (Awajun) and III (Porcelana) were associated with the Nacional cluster. The ancestry of the economically desired CCN 51 cultivar was revealed to be better assigned as 15% Amelonado, 13% Criollo, 25% Iquitos and 45% Awajun. The results of this study will improve the understanding of the genetic landscape in Peru, enhance genebank collections in Peru and enable the differentiation of the fine flavour industry in Peru. The new groups of cacao identified in this study will help understand the genetic structuring of cacao and represent a valuable new resource to search for valuable traits for breeding and commercialization programmes in the fine flavour cacao industry in Peru.